Associations of dipping and non-dipping hypertension with cardiovascular diseases in patients with dyslipidemia - Siping Dai (Termedia Publishing House, 2019)
Introduction Dyslipidemia combined with hypertension increases the risk of cardiovascular disease (CVD). The current study aimed to investigate the association of dipping and non-dipping hypertension with CVD in patients with dyslipidemia.